2007
DOI: 10.1111/j.1752-7325.2007.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Self‐Report of Oral Health in 4‐Year‐Old Pacific Children from South Auckland, New Zealand: Findings from the Pacific Islands Families Study

Abstract: Many mothers and their Pacific children have poor basic oral hygiene and dietary practices that increase the oral health risk in these children. Culturally appropriate and targeted strategies aimed at these modifiable practices need to be widely promoted so that the oral health burden carried by Pacific children can be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 5 publications
1
26
0
Order By: Relevance
“…Other countries reported percentages above ours, as in Nicaragua, which was 51.6% [27], 52.1% in Nigeria [31], 64% in Poland [28], 69% in Jordan [29], 72% in Spain [12], 88% in Thailand [30], close to 100% in Brazil [33], or in Sweden, where data have varied between 84% and 94% in several age groups [32]. Similarly, for various European countries, the USA, and Canada, reports ranged between 16–80% in boys and 26%–89% in girls [34,35], or 47% in socially disadvantaged groups in New Zealand [36]. In Mexico, Villalobos et al [39] observed a 56.3% prevalence of daily tooth brushing in schoolchildren from northwest Mexico, while in southeast Mexico community figures vary from 72% [40] to 82% [37,38] – percentages far higher than that observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other countries reported percentages above ours, as in Nicaragua, which was 51.6% [27], 52.1% in Nigeria [31], 64% in Poland [28], 69% in Jordan [29], 72% in Spain [12], 88% in Thailand [30], close to 100% in Brazil [33], or in Sweden, where data have varied between 84% and 94% in several age groups [32]. Similarly, for various European countries, the USA, and Canada, reports ranged between 16–80% in boys and 26%–89% in girls [34,35], or 47% in socially disadvantaged groups in New Zealand [36]. In Mexico, Villalobos et al [39] observed a 56.3% prevalence of daily tooth brushing in schoolchildren from northwest Mexico, while in southeast Mexico community figures vary from 72% [40] to 82% [37,38] – percentages far higher than that observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries report higher prevalence, with figures between 51.6% and 99.4% [27–33]. Data published for industrialized countries, including European countries, USA, and Canada, vary between 16–80% in boys and 26–89% in girls [12,34,35], to 47% in socially disadvantaged groups in New Zealand [36]. In Mexico, some differences have been observed in the prevalence reported among preschool and school age children, ranging from 56% to 81% [37–40].…”
Section: Introductionmentioning
confidence: 99%
“…In the above mentioned Myanmar community, ECC was considered inevitable and parents were not aware of the etiology (van Palenstein Helderman et al, 2006). Hence culturally appropriate and targeted strategies aimed at these modifiable practices need to be wisely promoted so that the oral health burden carried by these children can be reduced (Amin & Harrison, 2009;Schluter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…12 Many mothers and their Pacific children have poor basic oral hygiene and dietary practices that substantially increase the oral health risk in these children. 13 Traditional gift giving among Pacific families resident in New Zealand is an important issue. Although generally socially and economically disadvantaged, the majority of Pacific families made traditional gift commitments to family (often resident in the Pacific Islands) and the church.…”
Section: What Is Attrition Like?mentioning
confidence: 99%